From Biblioteca dei miei ragazzi to Gl’Istrici. Salani’s popular series of books for children - Dalila Forni (Ricerche di Pedagogia e Didattica, 2021)
This article traces the history of the Salani publishing house, focusing in particular on two famous series of the 20th century conceived for a young audience: Biblioteca dei miei ragazzi (1931-1955) and Gl'Istrici (1987). Though different from each other and coming from different historical periods, both series, which were very popular and appreciated by Italian readers, have been able to rethink children's literature and to evolve according to the readers' needs. In fact, Biblioteca dei miei ragazzi and Gl'Istrici have based their bibliographical selection not only on aesthetic and literary quality, but also on new proposals, new unconventional stories, frequently of international nature.  The series are therefore composed of books for boys and girls, teenagers and children, which are able to modernize the role of the reader and give a new literary and educational value to Italian children's literature through different editorial phases related to the historical moment of reference.